Unraveling the Complexity of the Gluten-Free Sugar-Free Diet: An Analysis of Parental Struggles in Providing Nutrition for Children with Special Needs - Bariyyah, Khairul; Siti Muniroh; Sri Andreani; Thomas Soseco (International Journal of Applied Guidance and Counseling, 2024)
This study aims to explore the level of parental knowledge regarding the Gluten-Free Sugar-Free (GFSF) diet and to identify the various challenges they face in its implementation for children with special needs. Using a quantitative survey approach, data were collected from 48 participating parents. Results showed that 50% of respondents had a high level of knowledge about the GFSF diet, 37.5% had moderate knowledge, and 12.5% had basic knowledge. No respondents had low knowledge. However, all respondents (100%) reported experiencing significant challenges in implementing the GFSF diet, including difficulties in accessing food ingredients, costs, and lack of practical knowledge. These findings indicate the need for more targeted interventions to support parents in overcoming these challenges, including improving the accessibility and affordability of GFSF products and providing educational programs tailored to their specific needs. This study provides important insights for developing effective strategies to support the health and well-being of children with special needs through the GFSF diet.